Self-Assembled PLGA-Pluronic F127 Microsphere for Sustained Drug Release for Osteoarthritis - Semee Seon; Yixian Li; Sangah Lee; Yoon Sang Jeon; Dong Seok Kang; Dong Jin Ryu (MDPI AG, 2024)
For many years, sustained-release drug delivery systems (SRDDS) have emerged as a featured topic in the pharmaceutical field. Particularly for chronic diseases, such as osteoarthritis, there is a lot of demand for SRDDS because of the long treatment period and repetitive medication administration. Thus, we developed an injectable PLGA-F127 microsphere (MS) that is capable of the in situ conversion to an implant. The microprecipitation method for PLGA-F127 MS was established, and the physicochemical stability of the products was confirmed. The microspheres were assembled into a single mass in 37 °C aqueous conditions and showed a remarkably delayed drug release profile. First, the release started with no significant initial burst and lagged for 60 days. After that, in the next 40 days, the remaining 75% of the drugs were constantly released until day 105. We expect that our PLGA-F127 MS could be employed to extend the release period of 2 months of medication to 4 months. This could be a valuable solution for developing novel SRDDS for local injections.